The effectiveness of image streaming method in improving anecdotal text writing skills for high school students - Jimat Susilo; Tazqiah Nuralizza; Lulu Ardiani Zain; Hesti Muliawati; Rimajon Sotlikova (Universitas Ahmad Dahlan, 2024)
This study aims to describe the ability of the results of writing anecdotal text using the image-streaming method and describe the influence of the image-streaming learning method in improving the ability to write anecdotal text. This study used quantitative methods. This type of research is a quasi-experimental research with a nonequivalent control group design model. The variables in This study are divided into two, namely the independent variable is the image-streaming learning method and the dependent variable is writing anecdotal text. The sample of this study amounted to 60 students divided into two groups, namely 30 students as an experimental class and 30 as a control class. Data collection is carried out by observation techniques and tests. The data of this study were analyzed with statistics assisted by the SPSS program. The results of this study show that students' ability to write anecdotal texts has increased. The use of the image streaming learning method provides stimulus to students in determining the framework for composing anecdotal texts so that students can write anecdotal texts well. In addition, the use of this image-streaming learning method has proven effective in improving students' ability to write anecdotal texts. Students are more motivated and active in learning.